International Criminal Law III: The Legacy of the ICTY and the ICTR - Svaček, Ondřej (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This chapter focuses on the legacy of the ICTY (International Criminal Tribunal for the former Yugoslavia) and the ICTR (International Criminal Tribunal for Rwanda), the ad hoc international criminal tribunals. It explores its creation, functioning, and termination and assesses the role given here to the UN Security Council. The contribution analyses the jurisdictional framework of both tribunals, their structure and procedural characteristics. It also stresses their importance for the development of international criminal law and points out the relevance and effect of their jurisprudence for the practice of their successors, namely the International Criminal Court. The contribution refers to the selected leading cases of the ICTY and the ICTR. Keywords: ICTY, ICTR, UN security council, jurisdiction, war crimes, crimes against humanity, Tadić, development of IHL (international humanitarian law), development of ICL (international criminal law), joint criminal enterprise, superior responsibility, article 21 Rome Statute